Growth and mortality of Cachana (Cynopotamus atratoensis) in the cienaga Grande de Lorica, Colombia - Charles Olaya-Nieto; Fredys Segura-Guevara; Antonio Vergara-Paternina (Revista MVZ Cordoba, 2015)
ABSTRACT